2016
DOI: 10.1071/he15127
|View full text |Cite
|
Sign up to set email alerts
|

How well are health information websites displayed on mobile phones? Implications for the readability of health information

Abstract: Issue addressed: More than 87% of Australians own a mobile phone with Internet access and 82% of phone owners use their smartphones to search for health information, indicating that mobile phones may be a powerful tool for building health literacy. Yet, online health information has been found to be above the reading ability of the general population. As reading on a smaller screen may further complicate the readability of information, this study aimed to examine how health information is displayed on mobile p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…The proliferation of mobile phones and their use has introduced a new avenue for engaging with people to help them with health and preventative measures. It has been found that 82% of mobile phone users in Australia have used their phones to search for health information and that 71% of health based web pages were mobile friendly . Mobile phones have been used previously in Australia to raise awareness of several public health issues, including monitoring of children's health, respiratory disease, sex education and nutrition .…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation of mobile phones and their use has introduced a new avenue for engaging with people to help them with health and preventative measures. It has been found that 82% of mobile phone users in Australia have used their phones to search for health information and that 71% of health based web pages were mobile friendly . Mobile phones have been used previously in Australia to raise awareness of several public health issues, including monitoring of children's health, respiratory disease, sex education and nutrition .…”
Section: Discussionmentioning
confidence: 99%
“…Almost 80% of Australians now use the internet as a source of health information, suggesting that the internet could be a powerful tool to educate and inform readers, with the potential to alleviate anxiety or concern [ 7 ]. As health models lean toward greater patient empowerment, patients may feel a greater sense of responsibility for their health care.…”
Section: Introductionmentioning
confidence: 99%
“…For example, website content may be more heterogeneous in countries such as the USA, which do not have organised screening. It would also be interesting to compare different platforms (eg, desktop websites vs mobile tailored versions), and to examine whether different design features (eg, information position68) affect information readability, saliency or users’ information seeking behaviour .…”
Section: Discussionmentioning
confidence: 99%